2018
DOI: 10.1186/s40463-018-0292-9
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study assessing the clinical utility of the Cottle maneuver in nasal septal surgery

Abstract: BackgroundA nasal septal deviation can have a significant detrimental effect on a patient’s quality of life. Nasal valve collapse (NVC) often co-exists with a septal deviation. The Cottle maneuver is one of the most common methods to diagnose NVC; however, no study has assessed the efficacy of this physical exam finding. This study tests the hypothesis that patients with nasal obstruction due to a septal deviation with a negative pre-operative Cottle maneuver will demonstrate a greater improvement in their Nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…Furthermore, false negatives can occur such as in the case of osteum internum fibrosis [15]. A recent study demonstrated no change in outcome in surgical success after a septoplasty in patients with either positive or negative Cottle Maneouver [16]. These results put into question the utility of the notion that patients with a positive Cottle Maneouver, when used as a single examination, truly benefit from anything more than a septoplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, false negatives can occur such as in the case of osteum internum fibrosis [15]. A recent study demonstrated no change in outcome in surgical success after a septoplasty in patients with either positive or negative Cottle Maneouver [16]. These results put into question the utility of the notion that patients with a positive Cottle Maneouver, when used as a single examination, truly benefit from anything more than a septoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as anatomy does not always correlate with obstruction for septal deviation and NVC, it may be important to determine novel outcome measures to assist in management [19]. The NOSE score is one outcome measure that may be used for this particular purpose [16]. In addition, it is unknown if certain tests are applicable to both types of collapse, and more studies are needed to evaluate methods to differentiate internal and external NVC.…”
Section: Discussionmentioning
confidence: 99%
“…the cheek skin lateral to the nasolabial fold is pulled laterally, increasing tension in the lateral nasal wall and thereby widening the nasal valve (15) . The result is positive if the patient reports improved breathing as a result of this.…”
Section: Examinationmentioning
confidence: 99%
“…Esta consiste en traccionar lateralmente la mejilla, lo que tensa la pared lateral nasal y abre la VNI. La prueba se considera positiva cuando el flujo aéreo inspiratorio por la fosa examinada mejora, lo que se observa en pacientes con válvulas estrechas o colapsadas 6 . Aunque muchas personas notarán cierto beneficio en el flujo nasal, en casos de colapso esta mejoría será sustancial.…”
Section: Evaluación Clínica Y Estudio De La Obstrucción Nasal De Origunclassified